Xenooplasmic Transfer between Buffalo and Bovine Enables Development of Homoplasmic Offspring - Chiaratti, Marcos Roberto; Ferreira, Christina Ramires [UNESP]; Meirelles, Flavio Vieira; Meo, Simone Cristina [UNESP]; Perecin, Felipe; Smith, Lawrence Charles; Ferraz, Marcio Leao; de Sa Filho, Manoel Francisco; Gimenes, Lindsay Unno; Baruselli, Pietro Sampaio; Gasparrini, Bianca; Garcia, Joaquim Mansano [UNESP] (Mary Ann Liebert, Inc., 2010)
Nuclear-mitochondrial incompatibilities may be responsible for the development failure reported in embryos and fetuses produced by interspecies somatic cell nuclear transfer (iSCNT). Herein we performed xenooplasmic transfer (XOT) by introducing 10 to 15% of buffalo ooplasm into bovine zygotes to assess its effect on the persistence of buffalo mitochondrial DNA (mtDNA). Blastocyst rates were not compromised by XOT in comparison to both in vitro fertilized embryos and embryos produced by transfer of bovine ooplasm into bovine zygotes. Moreover, offspring were born after transfer of XOT embryos to recipient cows. Buffalo mtDNA introduced in zygotes was still present at the blastocyst stage (8.3 vs. 9.3%, p = 0.11), indicating unaltered heteroplasmy during early development. Nonetheless, no vestige of buffalo mtDNA was found in offspring, indicating a drift to homoplasmy during later stages of development. In conclusion, we show that the buffalo mtDNA introduced by XOT into a bovine zygote do not compromise embryo development. on the other hand, buffalo mtDNA was not inherited by offspring indicating a possible failure in the process of interspecies mtDNA replication.